Core Biopsy of the Mediastinum with Video Assisted Thoracotomy Surgery Approach in Children Without One Lung Ventilation - Andre, Phillipus; Erlangga, M. Erias (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2025)
Video Assisted Thoracoscopy Surgery (VATS) is a minimally invasive procedure for diagnosing and treating intrathoracic disease. VATS will generate abnormal physiological changes including the presence of artificial pneumothorax so that anesthesia management in these patients requires an understanding those changes. In this case report discuss 4-year-old child, 15 kilograms with mediastinal mass suspected of thymoma underwent planned for core biopsy through VATS without one lung ventilation (OLV) due to equipment limitation. Preoperative he had no breathing problems, stable vital signs (O2 saturation 97-98% free air) with thoracic photographs and CT Scan of the mediastinal mass, and no signs of superior vena cava syndrome. Assessment of anesthesia ASA II, general anesthesia. Induction was performed using spontaneous breathing technique. Intraoperatively there was a period of desaturation up to 92% and increased EtCO2, which managed by increasing the oxygen fraction, PEEP, and increased respiration frequency. Operation lasted for 2 hours, bleeding 60cc. Postoperatively, patient was extubated in the operating room and admitted to intensive care. Pain management was done with ESP block and paracetamol IV. VATS mediastinal biopsy in children with mediastinal masses without OLV can be performed well with good understanding to ensure the safety of the patient.